2015
DOI: 10.4103/0019-509x.175843
|View full text |Cite
|
Sign up to set email alerts
|

Genomic profiling in a homogeneous molecular subtype of non-small cell lung cancer: An effort to explore new drug targets

Abstract: Results suggest, a potential role for PIK3CA, VEGFR2, RET and FGFR2 as therapeutic targets in EGFR non-mutated NSCLC that requires further clinical validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Overall, this can mean that the KDR mutation leads to high expression of KDR protein. In addition, KDR gene mutation has been previously reported to play a therapeutic role using Regorafenib in metastatic colon cancer [14] as well as in Nonsmall cell lung cancer [27]. On the contrary, it has also been reported to occur as an adverse effect of Ramucirumab therapy [28] and may lead to side effects when used with FGFR inhibitors for treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Overall, this can mean that the KDR mutation leads to high expression of KDR protein. In addition, KDR gene mutation has been previously reported to play a therapeutic role using Regorafenib in metastatic colon cancer [14] as well as in Nonsmall cell lung cancer [27]. On the contrary, it has also been reported to occur as an adverse effect of Ramucirumab therapy [28] and may lead to side effects when used with FGFR inhibitors for treatment.…”
Section: Discussionmentioning
confidence: 94%
“…It is important that the new genomic findings of the current study, demonstrating the occurrence of rare but recurrent somatic KDR/VEGFR2 mutations across common cancers, should be considered separately from studies correlating angiogenic responses with VEGF/VEGFR germline polymorphisms (18,19,20) , as well as from the published genetic screening studies that inaccurately reported the two VEGFR2 variants V297I and Q472H as likely pathogenic/cancer-driven KDR mutations (21,22) . V297I (rs2305948) and Q472H (rs1870377) are not cancer-exclusive mutations but non-pathogenic germline polymorphisms with allele frequencies between 10% and 20% across noncancerous-enriched populations from the 10,000 genomes (10) and EXAC (23) databases ( Figure S26).…”
Section: #4: -Genomic Findings Of New Kdr Somatic/tumor-exclusive/nonmentioning
confidence: 99%
“…Mutations of the EGFR gene constitute about 43%–89% of NSCLC cases, depending on the case series, rendering the affected patients candidates for targeted treatment with EGFR ‐TKIs . Although screening for EGFR mutation‐status is performed routinely, little is known about possible coexisting carcinogenic mechanisms in the population of patients featuring EGFR mutation.…”
Section: Introductionmentioning
confidence: 99%
“…Although screening for EGFR mutation‐status is performed routinely, little is known about possible coexisting carcinogenic mechanisms in the population of patients featuring EGFR mutation. Therapeutic benefits by the supplemental use of other biologicals to further improve survival and quality of life have become evident according to clinical trials, and some targeted agents are already used as first‐line treatment for selected patients with EGFR mutations . Gefitinib, erlotinib and afatinib today constitute the standard of care drugs incorporated in routine clinical management of EGFR ‐mutated lung cancers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation